(untitled) (Research, Society and Development, 2020)
This paper aims to investigate the extent to which the crisis experienced by the Brazilian economy in recent years (2014-2018) impacted the stock of formal jobs in medium-sized cities in Bahia, taking as a reference the information provided RAIS. The analysis records a mosaic of trends in the behavior of formal regional employment in Bahia outside the RMS, where the 20 medium-sized cities in Bahia are located. In these cities are distributed the main productive centers with their corporate life and their work stocks, which showed peculiar behaviors in the various dimensions addressed that reflect the specificities of each of their social systems, generating cost reduction by requiring lower wages in times of crisis but which are characterized by greater uncertainty among workers in the search for their survival.